The link between cutaneous allodynia and pain/sensitivity in teeth and gums during migraine episodes - Melis Yilmaz; Ediz Kale; Aynur Ozge (BMC, 2024)
Abstract Background Migraine is one of the most common primary headaches worldwide, while toothache is the most common pain in the orofacial region. The association of migraine pain, and oral pain is unknown. This study aims to investigate the association between migraine and dental and gingival pain with the presence of allodynia. Methods A questionnaire comprising demographic data with the ID-Migraine (IDM) tool, an Allodynia Symptom Checklist (ASC), and inquiries about pain and sensitivity in the teeth and gums during migraine attacks was administered to the participants and 762 responded the survey. The study classified participants based on the ASC, and the relationship between allodynia and pain/sensitivity in the teeth and/or gums during migraine attacks was analyzed. The statistical analyses utilized Chi-square tests and the Fisher-Exact test. Results Among 762 migraine patients, 430 (56.44%) were classified as allodynia (+), while 332 (43.56%) were classified as allodynia (−) (p < 0.001). Additionally, 285 participants (37.5%) reported experiencing pain and sensitivity in the teeth and gums during migraine attacks, with a significant relationship observed between allodynia and pain/sensitivity in the teeth and/or gums during migraine attacks (p < 0.001). Conclusion The findings of this study have important clinical implications. For migraine patients who are non-allodynic, the presence of pain and sensitivity in their teeth and gums during migraine attacks may indicate underlying dental diseases or the need for dental treatment especially root canal treatment. However, for allodynic patients, such symptoms may not necessarily indicate the presence of dental diseases or the need for dental treatment especially root canal treatment. These results underscore the significance of considering the presence of allodynia in the assessment and management of oral symptoms during migraine attacks.